2021
DOI: 10.1038/s41598-021-93228-2
|View full text |Cite
|
Sign up to set email alerts
|

Photoneuromodulation makes a difficult cognitive task less arduous

Abstract: A positive effect of photoneuromodulation (PNM) has been found on cognitive and emotional functions in healthy populations. However, the hemodynamic changes associated with improved cognitive functions (i.e., memory and executive functions) are unexplored. Therefore, the present study investigated the hemodynamic changes associated with PNM using functional near-infrared spectroscopy (fNIRS). In this experiment, 33 young healthy adults were recruited and randomly assigned to control and experimental groups. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
(36 reference statements)
3
11
0
Order By: Relevance
“…Such a decrease in HbO brain activation reflected that the participants paid less effort in terms of HbO in completing such a difficult task (i.e., 3-back task) after tPBM. Similar findings were also reported in previous studies [15], [52], [53]. For example, in a study on 18 older adults with mild cognitive impairment, Chan et al found that those who received active tPBM, compared to sham stimulation, exhibited reduced hemodynamic responses and meantime improved behavioral performance during a visual memory task [53].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Such a decrease in HbO brain activation reflected that the participants paid less effort in terms of HbO in completing such a difficult task (i.e., 3-back task) after tPBM. Similar findings were also reported in previous studies [15], [52], [53]. For example, in a study on 18 older adults with mild cognitive impairment, Chan et al found that those who received active tPBM, compared to sham stimulation, exhibited reduced hemodynamic responses and meantime improved behavioral performance during a visual memory task [53].…”
Section: Discussionsupporting
confidence: 84%
“…For example, in a study on 18 older adults with mild cognitive impairment, Chan et al found that those who received active tPBM, compared to sham stimulation, exhibited reduced hemodynamic responses and meantime improved behavioral performance during a visual memory task [53]. Furthermore, during a verbal 3-back task, Chan et al investigated frontal brain activity in healthy young adults and found significantly decreased frontal activation after tPBM [52]. As such, these combined studies support that the tPBM treatment could lead to improved neural function that thereby reduces the cognitive effort required to complete difficult tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The finding provided neural evidence for improvements in working memory as performing difficult tasks. As such, both a previous brain imaging study 24 and our current behavioral investigation support that tPBM reduces the cognitive efforts needed to complete tasks with high memory loads. Notably, for the 2-back task, the current study did not observe significant changes in the behavioral outcomes after single or seven-day repeated tPBM treatment.…”
Section: Discussionsupporting
confidence: 80%
“…Recently, one study from Chan et al. 24 specifically examined the hemodynamic changes during 0- and 3-back working memory tasks in young healthy adults after frontal tPBM stimulation (one duration for 350 s, three sections). The authors observed a significant reduction in frontal hemodynamic activation in the experimental group during the difficult task, i.e., the 3-back condition.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies have also investigated whether PBM may improve cognitive function in healthy participants. In this regard, human studies have shown improvements in attention and short-term memory (Barrett & Gonzalez-Lima, 2013;Vargas et al, 2017), executive function (Chan et al, 2021), and rule-based category learning (Blanco et al, 2017). Similarly, it has been shown that PBM may enhance attentional capabilities during a Go/No-Go task (Jahan et al, 2019).…”
Section: Introductionmentioning
confidence: 97%